Synthesis of disulfide-bonded outer membrane proteins during the developmental cycle of Chlamydia psittaci and Chlamydia trachomatis. - Hatch, T P (1986)
The disulfide bond cross-linked major outer membrane protein (MOMP) of the extracellular elementary bodies (EBs) of Chlamydia psittaci was reduced to its monomeric form within 1 h of entry of EBs into host cells by a process which was inhibited by chloramphenicol, while monomeric forms of three cross-linked cysteine-rich proteins could not be detected in Sarkosyl outer membrane complexes at any time in either extracellular or intracellular forms of C. psittaci. Synthesis and incorporation of the MOMP into outer membrane complexes were detected early in the infection cycle (12 h postinfection), while synthesis and incorporation of the cysteine-rich proteins were not observed until reticulate bodies had begun to reorganize into EBs at 20 to 22 h postinfection. By 46 h postinfection, the intracellular population of C. psittaci consisted mainly of EBs, the outer membrane complexes of which were replete with monomeric MOMP and cross-linked cysteine-rich proteins. Upon lysis of infected cells at 46 h, the MOMP was rapidly cross-linked, and infectious EBs were released. The status of the MOMP of intracellular Chlamydia trachomatis was similar to the status of the MOMP of C. psittaci in that the MOMP was largely uncross-linked at 24 and 48 h postinfection, but formed interpeptide disulfide bonds when it was exposed to an extracellular environment late in the developmental cycle. In contrast to C. psittaci, only a fraction of the cross-linked MOMP of infecting EBs of C. trachomatis was reduced by 4 h postinfection, and reduction of the MOMP was not inhibited by chloramphenicol. Exposure of extracellular EBs of C. trachomatis and C. psittaci to dithiothreitol reduced the MOMP but failed to stimulate metabolic activities normally associated with reticulate bodies.